Genetic architecture of recent-onset dilated cardiomyopathy in Moravian region assessed by whole-exome sequencing and its clinical correlates - Chaloupka, Anna; Piherova, Lenka; Grochova, Ilga; Binova, Jana; Krejci, Jan; Spinarova, Lenka; Stranecky, Viktor; Kmoch, Stanislav; Kubanek, Milos (Biomedical papers, 2019)
Aims: Recent-onset dilated cardiomyopathy (RODCM) is a disease of heterogeneous aetiology and clinical outcome. In this pilot study, we aimed to assess its genetic architecture and correlate genotype with left ventricular reverse remodelling (LVRR). Patients and Methods: In this multi-centre prospective observational study, we enrolled 83 Moravian patients with RODCM and a history of symptoms of less than 6 months, for whole-exome sequencing (WES). All patients underwent 12-month clinical and echocardiographic follow-up. LVRR was defined as an absolute increase in left ventricular ejection fraction > 10% accompanied by a relative decrease of left ventricular end-diastolic diameter > 10% at 12 months. Results: WES identified at least one disease-related variant in 45 patients (54%). LVRR occurred in 28 patients (34%), most often in carriers of isolated titin truncated variants, followed by individuals with a negative, or inconclusive WES and carriers of other disease-related variants (56% vs. 42% vs. 19%, P=0.041). Conclusion: A substantial proportion of RODCM cases have a monogenic or oligogenic genetic background. Carriers of non-titin disease-related variants are less likely to reach LVRR at 12- months than other individuals. Genetic testing could contribute to better prognosis prediction and individualized treatment of RODCM.
Keywords: dilated cardiomyopathy; familial cardiomyopathy; next generation sequencing; genetic architecture; cardiac remodelling